E-Procurement System Technology: An Analysis in Electronic Procurement Service Unit (LPSE) of Kepulauan Riau Province - Setyadiharja, Rendra; Budiman, Shahril; Karim, Zamzami A; Matridi, Raja Abumanshur; Junriana, Junriana; Ferizone, Ferizone; Nurmandi, Achmad (The Asian Journal of Technology Management (AJTM), 2014)
The practice of corruption always exist in public goods and service procurement in Indonesia. The Government efforts in reducing this case are doing new breakthrough like creating new system of service and goods procurement in an electronic way, usually called E-Procurement. After being instructed by Presidential Regulation number 54, year of 2010, the Local Government must use the E-Procurement System in the process of goods and service procurement, including Kepulauan Riau Province. This Research aims to analyzed the implementation of e-procurement system that had been adopted by Kepulauan Riau Province at year 2008. This research is not just for viewing the implementation of e-procurement system technically, but also to see how the influence of political process to the implementation of e-procurement. The Methodology used in this research is mix-method. This research are conducted in LPSE Kepulauan Riau Province, Procurement Service Unit (ULP) and also the vendors that supplies service and goods, that had been using the system. The results of this research are clearly stated that even the system of e-procurement of Kepulauan Riau Province are effective, and the political process is a factor which influencing the implementation of e-procurement.Keywords : E-Procurement, E-Procurement Implementation, Political Process, Principal Influence, Agent Influence.Â